2010
DOI: 10.1007/s12639-010-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunoaffinity chromatographic analysis for purification of specific diagnostic antigens of Paramphistomum epiclitum

Abstract: Polypeptide profile of somatic antigen of Paramphistomum epiclitum (PSAg) and Gastrothylax crumenifer (GSAg) was studied by SDS-PAGE. PSAg and GSAg showed 14 and 19 polypeptides in the range of 14.9-95.5 and 13.7-129.6 kDa with six common polypeptides of mol wt 16.8, 21.8, 23.7, 35.5, 43.4 and 70.8 kDa. P. epiclitum experimentally infected sheep sera were used for identification of specific immuno-dominant peptide in the range of 37-40 kDa against P. epiclitum by western blotting. Hyperimmune sera (HIS) was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…No polypeptide band showed immunoreactivity with the verified pooled negative serum Previous studies on Western blot analysis of somatic antigens of G. crumenifer (Saifullah et al, 2000;Saifullah et al, 2011), recorded low molecular weight polypeptides, ranging from <14 to 50 kDa. The results of studies on other trematodes are comparable with the current research, having identified somatic antigenic polypeptides of: F. hepatica in the range of 33 and 66 kDa (Gonenc et al, 2004); Paramphistomum cervi 52 kDa (Anuracpreeda et al, 2008); mixed infection with paramphistomes 90 kDa (Meshgi et al, 2009); and P. epiclitum with two lower molecular weight protein bands of 37.6 and 39.8 kDa (Arora et al, 2010). The studies on Paramphistomum spp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…No polypeptide band showed immunoreactivity with the verified pooled negative serum Previous studies on Western blot analysis of somatic antigens of G. crumenifer (Saifullah et al, 2000;Saifullah et al, 2011), recorded low molecular weight polypeptides, ranging from <14 to 50 kDa. The results of studies on other trematodes are comparable with the current research, having identified somatic antigenic polypeptides of: F. hepatica in the range of 33 and 66 kDa (Gonenc et al, 2004); Paramphistomum cervi 52 kDa (Anuracpreeda et al, 2008); mixed infection with paramphistomes 90 kDa (Meshgi et al, 2009); and P. epiclitum with two lower molecular weight protein bands of 37.6 and 39.8 kDa (Arora et al, 2010). The studies on Paramphistomum spp.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, studies on P. epiclitum recorded molecular weight bands in the ranges of 4-100 kDa (Jadav et al, 2018) and 14.9-95.5 kDa (Arora et al, 2010); in P. cervi the molecular weight band ranged from 12 to 100 kDa (Dar et al, 2016), and in Paramphistomum spp. the molecular weight band was in the 11.5-174 kDa range (Salib et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…The existence of crossreaction that occurred in helminthiasis infection could overcome by the use of purified proteins. The use of serological diagnosis techniques on a large scale could be done by using serum obtained from farms, abattoir and experimental animals to determine the level of sensitivity and specificity of the test (Arora et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The cattle and buffaloes postmortem examination showed positivity with other trematodes along with fasciolid infections and cross reactivity of 10 to 20% was observed for developed ELISA (Table 1). This may also explain with some common antigenic epitopes that are capable of detecting antigens from other trematodes (Arora et al, 2010).…”
Section: Elisamentioning
confidence: 93%